2019
DOI: 10.22502/jlmc.v7i1.285
|View full text |Cite
|
Sign up to set email alerts
|

Depression and its Associated Risk Factors among Residents of a Geriatric Home in Western Nepal

Abstract: Introduction: Elderly people suffer from many acute and chronic illnesses and also show higher prevalence of depression. The trend of old age homes is rising in Nepal. The aim of this study was to assess depression in the residents of a geriatric home and compare it to that in the elderly population living in their own homes. Methods: This was an observational cross-sectional study in which residents of a geriatric home above 60 years of age were selected as cases, and those living in their own homes were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Our study found that age and marital status did not have an effect on the depression levels of elderly individuals living in the nursing home. This is supported by the results of Pokharel et al (23). However, it is generally believed that depression in the elderly is influenced by age and marital status (24,25).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our study found that age and marital status did not have an effect on the depression levels of elderly individuals living in the nursing home. This is supported by the results of Pokharel et al (23). However, it is generally believed that depression in the elderly is influenced by age and marital status (24,25).…”
Section: Discussionsupporting
confidence: 63%
“…However, it is generally believed that depression in the elderly is influenced by age and marital status (24,25). Research suggests that single individuals between the ages of 70-74 are more likely to experience depression while residing in nursing homes (23)(24)(25)(26)(27). In Türkiye, cultural norms and circumstances may lead elderly individuals, who have lost their spouses, to choose or be required to reside in nursing homes, despite not being a common situation.…”
Section: Discussionmentioning
confidence: 99%
“…This study included 315 participants aged 40 years and older, of whom 41% had hypertension, which is consistent with earlier studies. 2,4 However, a study conducted in the Palpa district of Nepal reported a lower prevalence of hypertension (22%), indicating regional differences in hypertension prevalence 17 . Our findings indicated that older age significantly increased the risk of hypertension, particularly among those aged 70 years and older, which aligns with previous literature.…”
Section: Discussionmentioning
confidence: 99%